Gut microbiota: a new angle for traditional herbal medicine research. Issue 30 (7th June 2019) - Lin, Longfei; Luo, Liyu; Zhong, Ming; Xie, Tanggui; Liu, Yuling; Li, Hui; Ni, Jian
Abstract : Traditional Herbal Medicine (THM) has been used for thousands of years, and is popular worldwide due to its effectiveness in a variety of diseases. Abstract : Traditional Herbal Medicine (THM) has been used for thousands of years, and is popular worldwide due to its effectiveness in a variety of diseases. THM has also formed the basis of the discovery of modern drugs like artemisinin and paclitaxel. However, at present, studies that focus on development in the field of THM are stagnant because currently, the effective ingredients in the herbal formulations and the ambiguity of the underlying mechanisms of action are unknown. In this review, we have investigated the studies available that focused on the efficacy, active ingredients and bioavailability of THM, and the function of gut microbiota in THM-mediated treatment of disease. We hypothesized that most THMs treat diseases via three mechanisms: (1) metabolizing into active metabolites by the action of gut microbiota, (2) regulation of gut microbiota balance, and (3) regulating the fermentation products of the gut microbes. Therefore, focusing on these aspects can help elucidate the pharmacodynamic constituents of THM preparations, and their therapeutic mechanisms of action.